Estudio comparativo de las complicaciones perinatales en gestantes nulíparas añosas y normales atendidas en el Hospital Isidro Ayora Loja - Cuenca Romero, Rocío del Carmen (2013)
The late motherhood is generally associated with complications of pre-existing diseases that increase with the age and dependent with pathologies of pregnancy, which causes that they are considered high-risk pregnancies that will bring complications for the binomial maternal-fetal, therefore the partnership was established between the age of conception of the first child and the maternal and perinatal complications, determining if the advanced maternal age is a factor of high risk, knowing that complications occur in primipara unlosable and identifying complications of the neonates of primigravidas older than 30 years. This was a descriptive study, prospective, cross sectional; using an instrument data was recorded to primigravidas 20-40 years served in the area of the Hospital Gineco-Ostetricia Isidro Ayora Loja from 1 March to 31 August 2013, with a universe of 1514 patients were taken as a sample 168 who were the ones who met the inclusion criteria. In pregnant women of 20-24 years was the most frequent complication Preeclampsia with 13.64 % in their newborns prevailed fetal distress with 12.50 %. Between the 25-29 years the prevailing risk for preterm delivery with 16.13 %, in their newborns prematurity with 16.13 %. Between the 30-34 years prevailed the preeclampsia and urinary tract infections with 12.12 %, the newborns had prematurity with 6.06 %. Between the 35-40 years the prevailing pregnancy-induced hypertension with 25.00 %, in the neonates meconial aspiration syndrome, small for gestational age, prematurity, respiratory distress syndrome type I and type II with 6.25 %. It was concluded that in all ages the pregnant woman and your product are prone to complications, thus increasing the incidence of cesarean sections, perinatal and maternal morbidity, therefore should be considered to the primigravida trekker as a high-risk pregnancy in our institution. Key Words: Primigravidas older than 35 years. Advanced maternal age and pregnancy. Delayed maternity.